Pemahaman Orang Tua terhadap Pola Makan Anak Penderita Kanker di RSUP Prof Dr. R. D. Kandou Manado - Rompies, Ronald; Tatara, Hubert I; Gunawan, Stefanus (Universitas Sam Ratulangi, 2020)
Abstract: Information about nutrition and parentsâ€™ experience are very important in supporting the nutrition of children with cancer. This study was aimed to obtain the parentsâ€™ understanding about nutrition of children with cancer. We used modified structured questionnaire about diet and sanitation which were already validation testing. The results showed that there were 38 complete questionnaires consisted of acute lymphoblastic leukemia (ALL) in 14 children (36.8%), followed by acute myeloid leukemia (AML) in 8 children, and retinoblastoma in 7 children. The majority of parents were housewives (84%) meanwhile senior high school educated was the most common education (57.8% of mothers and 52.6% of fathers)). All parents changed the diet style of their children after diagnosed as cancer. Most parents (78.9%) answered that food could cause cancer, and (94.7%) avoided certain foods; (78.9%) chose junk food as avoided food; and during treatment, (89.4%) gave special foods which were high protein, fruits, vegetables, and milk. Most parents (94.7%) answered that children with cancer had to avoid street foods, and (94.7%) chose mineral water as a safe drink. In conclusion, education of medical workers about nutrition of children with cancer is needed to achieve agreement in optimal nutrition.Keywords: nutrition of children with cancerÂ Abstrak: Informasi mengenai kebutuhan nutrisi dan pengalaman orang tua berperan penting dalam menunjang nutrisi anak dengan kanker. Penelitian ini bertujuan untuk mengetahui pemahaman orang tua tentang nutrisi yang optimal bagi anak dengan kanker. Pada penelitian ini digunakan kuesioner terstruktur tentang diet dan kebersihan yang dimodifikasi, teruji dengan validitas isi. Hasil penelitian mendapatkan 38 kuesioner yang diisi lengkap, dengan diagnosis terbanyak acute lymphoblastic leukemia (ALL) pada 14 anak (36,8%), diikuti acute myeloid leuke-mia (AML) 8 anak, dan retinoblastoma 7 anak. Mayoritas orang tua memiliki pekerjaan ibu rumah tangga (84%) dan pendidikan terakhir yang terbanyak ialah SMA (ibu 57,8% dan ayah 52,6%). Semua orang tua merubah pola makan anak mereka setelah terdiagnosis kanker. Sebagian besar orang tua (78,9%) menjawab makanan dapat menyebabkan kanker dan (94,7%) menghindari makanan tertentu; (78,9%) memilih junk food sebagai makanan yang harus dihindari; dan (89,4%) memberikan makanan khusus selama pengobatan mengandung tinggi protein, buah, sayur, dan susu. Sebagian besar orang tua (94,7%) menjawab anak penderita kanker tidak boleh makan makanan di pinggir jalan, dan (94,7%) memilih air mineral sebagai minuman yang aman untuk diminum. Simpulan penelitian ialah perlu dilakukan edukasi dan penyuluhan oleh tenaga medis tentang nutrisi untuk anak kanker agar terdapat kesepahaman dalam pemberian nutrisi yang optimal.Kata kunci: nutrisi anak dengan kanker